Effect of quercetin on the progression of breast cancer in mice with chronic stress by regulating the polarization of microglia - Tianyu Luo; Yuqi Liang; Liushan Chen; Haidong Sun; Qianjun Chen (Journal of Functional Foods, 2024)
The development breast cancer is closely related to emotional factors such as chronic stress. Evidence from preclinical studies suggests that microglia play a key role in depression and stress. Quercetin is a bioactive flavonoid with a wide range of pharmacological effects. This study explores the effect and mechanism of quercetin on microglia in the treatment of chronic stress breast cancer. Our results show that quercetin could improve depressive behavior in chronic stress mice, the expression of STAT1 in microglia and the sympathetic nervous system activity in tumor was inhibited by quercetin. While after microglia silencing, quercetin has no significant effect on the growth and malignancy of breast cancer induced by chronic stress. Quercetin could inhibit the promotion of chronic stress on breast cancer tumor and did not act on the tumor ifself, but may affect the tumor by modulating microglia as well as the tumor sympathetic infiltration.